Pengaruh Marketing Relationship Dan Technician Performance Terhadap Kepuasan Pelanggan : Studi Pada PT Jaya Kencana Divisi Lift Eskalator Servis - Reno Ba'i Kurniawan; Herudini Subariyanti (Journal of Management and Social Sciences, 2023)
PT Jaya Kencana is a company engaged in the field of mechanical and electrical contractors. One of the divisions at PT Jaya Kencana is engaged in the elevator escalator service division. This division is a division that offers elevator and escalator maintenance services. Where in this division the level of customer satisfaction is needed for the progress of the company. The independent variables in this study are marketing relationships and technician performance. The dependent variable in this study is customer satisfaction. The research uses statistical quantitative methods by determining the minimum number of samples using the slovin formula. The sample in this study was 101 respondents. Marketing relationship has a t count > t table (3.932 > 1.9844) with a significant value of 0.00 <0.05, which means that marketing relationships have an effect on customer satisfaction. Technician performance has a t count > t table (5.530 > 1.9844) with a significant value of 0.00 <0.05, which means that technician performance has an effect on customer satisfaction. Marketing relationship and technician performance have a significant value of 000 <0.05 and F count > F table (160.776 > 3.94), which means that marketing relationship and technician performance have a significant simultaneous effect on customer satisfaction. The results of this study can be used as input for related companies and can be used as an evaluation to increase company customer satisfaction.